1992
DOI: 10.1071/pp9920353
|View full text |Cite
|
Sign up to set email alerts
|

T-DNA Insertion Mutagenesis in Arabidopsis: Prospects and Perspectives

Abstract: Approximately 13 000 independent transformants of Arabidopsis have been generated utilising the Agrobacterium-mediated seed infection/transformation procedure. The average number of functional independent T-DNA insertion events per transformed line is 1.5, thus constituting a population with 19 500 independent inserts. These transformed lines have been screened under two environmental regimes for visible alterations in phenotype. In one screen the lines were grown under greenhouse conditions and examined at we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 27 publications
1
64
0
Order By: Relevance
“…These frequencies are relatively low compared with those found by us for Z~gus activation in post-embryonic organs such as leaves (28%), roots (30%) or floral organs (22%), which may be a reflection either of the relative number of genes expressed in the respective organs, or of the possible low levels of expression of Agus fusions in early embryos, or of a bias into the types of genes into which T-DNA inserts, as discussed previously . Insertional mutagenic studies by Forsthoefel et al (1992) on large populations of transgenic Arabidopsis found a frequency of embryonic lethals of 1-5.8%, although particular transformants may contain multiple T-DNA inserts, and only a relatively small proportion of mutants may be due to T-DNA insertion events (Errampalli et al, 1991). Further information on the nature of the proteins encoded by the tagged genes is required before we can consider their functions.…”
Section: Embryonic Markers In Arabidopsis 901mentioning
confidence: 99%
“…These frequencies are relatively low compared with those found by us for Z~gus activation in post-embryonic organs such as leaves (28%), roots (30%) or floral organs (22%), which may be a reflection either of the relative number of genes expressed in the respective organs, or of the possible low levels of expression of Agus fusions in early embryos, or of a bias into the types of genes into which T-DNA inserts, as discussed previously . Insertional mutagenic studies by Forsthoefel et al (1992) on large populations of transgenic Arabidopsis found a frequency of embryonic lethals of 1-5.8%, although particular transformants may contain multiple T-DNA inserts, and only a relatively small proportion of mutants may be due to T-DNA insertion events (Errampalli et al, 1991). Further information on the nature of the proteins encoded by the tagged genes is required before we can consider their functions.…”
Section: Embryonic Markers In Arabidopsis 901mentioning
confidence: 99%
“…All seed were surface sterilized (Forsthoefel et al, 1992) and plated onto Murashige and Skoog (1962) agar (4.3 g/L Murashige and Skoog salts [Sigma, Poole, UK], 1% sucrose, and 1% bacto-agar, pH 6.0, with 1 M KOH), with the exception of transgenic CycB1:1:GUS seed, which were germinated on Hoagland medium with 0.1% sucrose (Beemster and Baskin, 1998). The plates were placed at 4ЊC for 48 hr and then in constant white light at 22ЊC.…”
Section: Growth Of Arabidopsis Thaliana Seedlingsmentioning
confidence: 99%
“…Although most male sterility genes and their wild-type alleles have not been cloned and studied (Aarts et al, 1993), phenotypic and histological analyses suggest that some male sterility mutations affect the differentiation and/or function of many anther cell types, including those in the stomium, tapetum, endothecium, and the archesporial and sporogenous layers of the anther primordium (Kaul, 1988;Chaudhury, 1993, this issue). Arabidopsis malesterile mutants are easy to identify because they flower for a longer time period, grow taller, and remain in a green or nonsenesced state longer than their male-fertile, wild-type counterparts (Feldmann, 1991;Chaudhury et al, 1992;Forsthoefel et al, 1992;Aarts et al, 1993;Preuss et al, 1993). Because large numbers of mutagenized plants can be screened readily (Feldmann, 1991;Chaudhury et al, 1992;Forsthoefel et al, 1992), genetic studies in Arabidopsis have the potential to dissect gene pathways that control both the histodifferentiation program (phase 1) and the dehiscence and cell degeneration program (phase 2) of anther development (Figure 1).…”
Section: Male-sterile Mutants Can Be Used To Genetically Dissect Anthmentioning
confidence: 99%
“…Arabidopsis malesterile mutants are easy to identify because they flower for a longer time period, grow taller, and remain in a green or nonsenesced state longer than their male-fertile, wild-type counterparts (Feldmann, 1991;Chaudhury et al, 1992;Forsthoefel et al, 1992;Aarts et al, 1993;Preuss et al, 1993). Because large numbers of mutagenized plants can be screened readily (Feldmann, 1991;Chaudhury et al, 1992;Forsthoefel et al, 1992), genetic studies in Arabidopsis have the potential to dissect gene pathways that control both the histodifferentiation program (phase 1) and the dehiscence and cell degeneration program (phase 2) of anther development (Figure 1).…”
Section: Male-sterile Mutants Can Be Used To Genetically Dissect Anthmentioning
confidence: 99%
See 1 more Smart Citation